Strict Major Histocompatibility Complex Molecule Class-Specific Binding by Co-Receptors Enforces MHC-Restricted αβ TCR Recognition during T Lineage Subset Commitment - Li, Xiao-long; Teng, Mai-kun; Reinherz, Ellis L.; Wang, Jia-huai (Frontiers in Immunology, 2013)
Since the discovery of co-receptor dependent αβTCR recognition, considerable effort has been spent on elucidating the basis of CD4 and CD8 lineage commitment in the thymus. The latter is responsible for generating mature CD4 helper and CD8αβ cytotoxic T cell subsets. Although CD4+ and CD8+ T cell recognition of peptide antigens is known to be MHC class I- and MHC class II-restricted, respectively, the mechanism of single positive (SP) thymocyte lineage commitment from bipotential double positive (DP) progenitors is not fully elucidated. Classical models to explain thymic CD4 versus CD8 fate determination have included a stochastic selection model or instructional models. The latter are based either on strength of signal or duration of signal impacting fate. More recently, differential co-receptor gene imprinting has been shown to be involved in expression of transcription factors impacting cytotoxic T cell development. Here, we address commitment from a structural perspective, focusing on the nature of co-receptor binding to MHC molecules. By surveying 58 MHC class II and 224 MHC class I crystal structures in the Protein Data Bank (PDB), it becomes clear that CD4 cannot bind to MHC I molecules, nor can CD8αβ or CD8αα bind to MHC II molecules. Given that the co-receptor delivers Lck to phosphorylate exposed CD3 ITAMs within a peptide/MHC (pMHC)-ligated TCR complex to initiate cell signaling, this strict co-receptor recognition fosters MHC class-restricted SP thymocyte lineage commitment at the DP stage even though both co-receptors are expressed on a single cell. In short, the binding preference of an αβTCR for a peptide complexed with an MHC molecule dictates which co-receptor subsequently binds, thereby supporting development of that subset lineage. How function within the lineage is linked further to biopotential fate determination is discussed.